1976
DOI: 10.1530/acta.0.0810801
|View full text |Cite
|
Sign up to set email alerts
|

RELATIONSHIP BETWEEN OESTROGEN, PROSTAGLANDIN F2α AND HISTAMINE IN DELAYED IMPLANTATION IN THE MOUSE

Abstract: Treatment of pregnant mice ovaricctomized on day 3 (23.00-2330 h) with progesterone (1 mg/day/mouse, from day 4 through 11 post coitum (p.c.)) and oestrogen (single injection of 0.05 \g=a\g on day 8 p. c.) induced implantation in all the animals. Implantation was inhibited in animals following three subcutaneous injections of indomethacin given on the morning and afternoon of day 8 and the morning of day 9 p. c. A single injection of histamine on day 8 p. c. partially compensated the effect of indomethacin. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 11 publications
(14 reference statements)
1
30
0
Order By: Relevance
“…of Ptgs by NSAIDs leads to either complete or partial delay in implantation (1)(2)(3)(4)(5)43). These observations were supported by an infertility phenotype of Ptgs2 null mice (13).…”
Section: Isoform-specific Ptgs Inhibition Alters Embryo Implantation mentioning
confidence: 80%
See 4 more Smart Citations
“…of Ptgs by NSAIDs leads to either complete or partial delay in implantation (1)(2)(3)(4)(5)43). These observations were supported by an infertility phenotype of Ptgs2 null mice (13).…”
Section: Isoform-specific Ptgs Inhibition Alters Embryo Implantation mentioning
confidence: 80%
“…However, unlike mice that showed only mesometrial stromal expression of Ptgs2 on the day 6 implantation site, hamsters showed Ptgs2 expression in decidual cells (PDZ cells) immediately surrounding the implanting embryo. Expression of Ptgs2 in cells of the PDZ of days 5 and 6 and its expression in trophoblast cells of the growing embryo on later days of pregnancy suggest that Ptgs2 could not only be associated with inflammatory aspects of implantation 2 but also be involved in protection of the embryo proper by its immunomodulatory and cell-cell barrier formation properties (55,56). In rodents, implantation is followed by loss of uterine luminal epithelial cells and their barrier functions just around the implanted embryo (42).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations